Portsmouth Peace Treaty of 1905 in Assessments of Russian Public Opinion - A. A. Sorokin; Yu. V. Sokolov (Научный диалог, 2025)
This article presents a novel examination of the evaluations made by various political factions within Russian society — liberal, conservative, and populist — regarding the Portsmouth Peace Treaty of 1905. The research is based on materials from central Russian periodicals. The authors elucidate the essence and content of the positions articulated by the Russian press concerning the necessity of concluding a peace treaty with Japan. It is demonstrated that connections were drawn in the periodical press between the establishment of peace and the domestic political crisis in Russia. The article characterizes opinions expressed in periodicals regarding the mediation of the United States in the conclusion of the peace treaty between Russia and Japan. Furthermore, it analyzes the perspectives of leading newspapers and journals on territorial concessions made by Russia, including discussions surrounding the status of territories in the Kwantung region and the division of Sakhalin Island. The article also explores how periodicals envisioned Russia’s status in the Far East and the shifting influence of various powers on regional politics following the signing of the Portsmouth Treaty.